Prevalência de streptococcus agalactiae de gestantes em Sergipe - Oliveira, Jordão Santana de (2017)
Neonatal infections are still a major challenge for Pediatrics and Obstetrics despite advances in fetal medicine. Among the infectious agents, Streptococcus agalactiae or Streptococcus group B (GBS) of Lancefield, which are responsible for sepsis, meningitis, and neonatal pneumonia, should be highlighted. The objective of this study was to evaluate the colonization of GBS in pregnant women in the third trimester of pregnancy attended at prenatal services at the João Cardoso Nascimento Junior University Hospital, at the Center for Comprehensive Health Care for Women (CAISM), at the Center for Medical Specialties Of Aracaju-CEMAR, and in the Basic Health Unit Gov. Antônio Carlos Valadares in São Cristovão-SE. The collection of vaginal and anorectal secretions was preceded by the application of a questionnaire with sociodemographic and obstetric data. A total of 68 samples were taken between April 25 and October 31, 2016. The samples obtained were inoculated in Todd-Hewitt Broth and subsequently subcultured in blood agar plates. The CAMP test (Christie, Atkins, Munch-Petersen) was used to identify the GBS. Among the 68 pregnant women evaluated, 38 (55.8%) presented a positive culture for Streptococcus agalactiae. The sociodemographic variables and the gynecological-obstetric history were studied.